SEeking AnsweRs for Care Homes during the COVID-19 pandemic (COVID SEARCH) - Spilsbury, Karen (Age Ageing, 2020)
The care and support of older people residing in long-term care facilities during the COVID-19 pandemic has created new and unanticipated uncertainties for staff. In this short report, we present our analyses of the uncertainties of care home managers and staff expressed in a self-formed closed WhatsApp™ discussion group during the first stages of the pandemic in the UK. We categorised their wide-ranging questions to understand what information would address these uncertainties and provide support. We have been able to demonstrate that almost one-third of these uncertainties could have been tackled immediately through timely, responsive and unambiguous fact-based guidance. The other uncertainties require appraisal, synthesis and summary of existing evidence, commissioning or provision of a sector- informed research agenda for medium to long term. The questions represent wider internationally relevant care home pandemic-related uncertainties.